Chlorhexidine gluconate 0.2% as a treatment for recalcitrant fungal keratitis in Uganda: a pilot study. Issue 1 (5th July 2021) - Arunga, Simon; Mbarak, Tumu; Ebong, Abel; Mwesigye, James; Kuguminkiriza, Dan; Mohamed, Abeer; Hoffman, Jeremy John; Leck, Astrid; Hu, Victor; Burton, Matthew
Abstract : Objective: Fungal keratitis is a major ophthalmic public health problem, particularly in low-income and middle-income countries. The options for treating fungal keratitis are limited. Our study aimed to describe the outcomes of using chlorhexidine 0.2% eye-drops as additional treatment in the management of patients with recalcitrant fungal keratitis. Methods: This study was nested within a large cohort study of people presenting with microbial keratitis in Uganda. We enrolled patients with recalcitrant fungal keratitis not improving with topical natamycin 5% and commenced chlorhexidine 0.2%. Follow-up was scheduled for 3 months and 1 year. The main outcome measures were healing, visual acuity and scar size at final follow-up. Results: Thirteen patients were followed in this substudy. The patients were aged 27–73 years (median 43 years). Filamentous fungi were identified by microscopy of corneal scrape samples in all cases. Isolated organisms included Aspergillus spp, Fusarium spp, Candida spp, Bipolaris spp and Acremoninum spp. At the final follow-up, nine patients (75%) had healed; three had vision of better than 6/18. Three patients lost their eyes due to infection. In the remaining nine cases, corneal scarring was variable ranging from 4.6 to 9.4 mm (median 6.6 mm, IQR 5.9–8.0 mm); of these five had dense scars, three had moderate scars and one had a mild scar. None of the patients demonstrated signs of chlorhexidine toxicity during the follow-up. Conclusion: Chlorhexidine 0.2% was found to be a useful sequential adjunctive topical antifungal in cases of fungal keratitis not responding to natamycin 5%, which warrants further evaluation.